(Natural Flavor: Production, Sources, Isolation and Recovery Techniques) - Junaidi, Lukman (Warta Industri Hasil Pertanian, 2008)
A flavor is a substance which may be a single chemical entity, or a blend of chemicals of natural or synthetic origin whose primary purpose is to provide all or part of the particular flavor effect to any food or other product take in the mouth. A vast array of compounds may be responsible for the aroma of the food products, such as alcohols,aldehydes, eesters,dicarbonyls, short to medium-chain free fatty acids, methyls ketones, lactones, phenolic compounds.At present, due to the high cost or lack of availability of natural flavor extracts, most commercial flavorants are chemically synthesized, mostly from petroleum-derived precursors. Because chemical synthesis often uses environmentally unfreiendly production processes, it is desirable to switch to bioproduction, including the extraction from natural source, de novo microbial process (fermentation ), and bioconversion of natural precursos using micro-organisms or isolated enzymes.Natural flavour compounds usually exist at very low concentratiuons. To recover the flavour compounds at a purity of interest for practicial applications , flash distillation and adsorption are being used degradation as wellas high energy cosumption. These challenges inspire and encourage the development of a safer and more economical separation technique, such as: pervaporation techniques, head-space techniques, and supercritical fluid extraction.The scope of this paper covers the development in the bioflavor production, sources, isolation and recovery techniques.This paper is aimed at providing the information related on natural flavor issue which can be used as an additional information to the researcher on the natural falvor industry.